2023
DOI: 10.1021/acs.jpcc.3c01388
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Synthesis of Electrochemically Active Titanium Diboride-Based Nanosheets by High-Energy Ball Milling

Abstract: AlB2-type layered metal diborides have sought renewed research attention in recent years on account of their ability to yield XBenestheir quasi-two-dimensional (2D) counterparts. These quasi-2D nanostructures present exciting avenues to utilize the rich science offered by metal diborides. While a range of approaches have been developed to exfoliate layered metal diborides, the ability to obtain XBenes in a scalable manner is in its incipient stagesthis is a critical bottleneck in translating their rich nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Specifically, MgB 2 is the most explored metal diboride where these methods are utilized for exfoliation. Further, mechanical ball milling has emerged as a prominent method for exfoliating layered materials. ,, This technique takes advantage of high rotational speeds during the milling processes, leading to rapid collisions within the bulk material. These collisions generate shear and vertical impact forces, aiding in the exfoliation process.…”
Section: Research Trends In Alb2-type Metal Diborides and Xbenesmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, MgB 2 is the most explored metal diboride where these methods are utilized for exfoliation. Further, mechanical ball milling has emerged as a prominent method for exfoliating layered materials. ,, This technique takes advantage of high rotational speeds during the milling processes, leading to rapid collisions within the bulk material. These collisions generate shear and vertical impact forces, aiding in the exfoliation process.…”
Section: Research Trends In Alb2-type Metal Diborides and Xbenesmentioning
confidence: 99%
“…One of the earliest MgB 2 nanosheet experimental realizations was made in 2015 by Das and colleagues . Researchers worldwide have synthesized 2D nanostructures from AlB 2 -type metal borides primarily by top-down approaches such as chemical exfoliation, , ultrasonication, , cation exchange, dissolution and recrystallization process, , cosolvent exfoliation, , and mechanical ball milling. , …”
Section: Research Trends In Alb2-type Metal Diborides and Xbenesmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that nanosheets from TiB 2 can be derived by dissolution and recrystallization, 16 cosolvent-assisted exfoliation, 23 surfactant-assisted exfoliation, 36 and, very recently, mechanical exfoliation. 37 Among these methods, dissolution and recrystallization was our first attempt at exfoliating TiB 2 . The uniqueness of this method lay in the fact that rather than a top-down exfoliation process, TiB 2 crystals underwent a complete dissolution in aqueous hydrogen peroxide and later recrystallized by way of laterally oriented attachment into quasi 2D sheets.…”
Section: ■ Introductionmentioning
confidence: 99%